Latin American Central Bank Reform : Progress and Challenges. (IMF Working Papers; Working Paper, 2005)
This study takes stock of the institutional reform of monetary policy in Latin America since the early 1990s. It argues that strengthening the legal independence of central banks, together with macroeconomic policies, was instrumental in reducing inflation from three-digit annual rates in the 1990s to single-digit territory in 2004. The paper also discusses the main challenges of monetary policy today, namely, achieving price stability, restoring market confidence in domestic currencies, and sticking to policy consistency despite adverse effects of the volatility of capital flows. Finally, recurrent banking crises and lack of fiscal discipline are identified as the main risks for the success of monetary policy in Latin America.